Improved light microscopy counting method for accurately counting Plasmodium parasitemia and reticulocytemia. Issue 8 (24th May 2016) - Lim, Caeul; Pereira, Ligia; Shardul, Pritish; Mascarenhas, Anjali; Maki, Jennifer; Rixon, Jordan; Shaw‐Saliba, Kathryn; White, John; Silveira, Maria; Gomes, Edwin; Chery, Laura; Rathod, Pradipsinh K.; et al.
Abstract : Even with the advances in molecular or automated methods for detection of red blood cells of interest (such as reticulocytes or parasitized cells), light microscopy continues to be the gold standard especially in laboratories with limited resources. The conventional method for determination of parasitemia and reticulocytemia uses a Miller reticle, a grid with squares of different sizes. However, this method is prone to errors if not used correctly and counts become inaccurate and highly time‐consuming at low frequencies of target cells. In this report, we outline the correct guidelines to follow when using a reticle for counting, and present a new counting protocol that is a modified version of the conventional method for increased accuracy in the counting of low parasitemias and reticulocytemias. Am. J. Hematol. 91:852–855, 2016. © 2016 Wiley Periodicals, Inc.